Asymmetry as a Factor Weakening Resilience and Integration in the Sustainable Development of the Polish-Czech Borderland in the Context of the Dispute About the Turów Mine - Łaźniewska, Ewa; Boháč, Artur; Kurowska-Pysz, Joanna (Problemy Ekorozwoju, 2023)
By analysing asymmetry in socioeconomic and environmental development in the Polish-Czech borderland, we contribute to the discussion on its impacts as a factor weakening resilience and integration for the purposes of sustainable development in the region. In the article, we use the results of the studies under the Project The crisis at the Turów Mine and its impact on Czech-Polish cross-border cooperation: An evaluation, conclusions and recommendations, funded by the Polish National Agency for Academic Exchange in 2022. The main aim of our research is to draw conclusions for territorial self-governments as to how they should strengthen sustainable development based on integration with foreign partners, thus enhancing resilience. We draw conclusions based on qualitative research, statistical analyses and literature studies. One of the key conclusions which can be drawn from the present study is that the asymmetry visible in many socioeconomic areas weakens the resilience of institutional structures to crises, resulting in barely discernible cooperation between these regions.